2019
DOI: 10.1016/j.trci.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging measures of brain atrophy from the EXPEDITION3 trial in mild Alzheimer's disease

Abstract: Introduction Solanezumab is a humanized monoclonal antibody that preferentially binds to soluble amyloid β and promotes its clearance from the brain in preclinical studies. The objective of this study was to assess the effect of solanezumab in slowing global and anatomically localized brain atrophy as measured by volumetric magnetic resonance imaging (MRI). Methods In the EXPEDITION3 phase 3 trial, participants with mild Alzheimer's disease were randomized to receive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Intravenous immunoglobulin is obtained from plasma of healthy donors and is made up of human Abs mainly of the IgG-type. 5,74 Nevertheless, the first completed phase 3 trial of IVIg as a treatment for AD demonstrated good tolerability but lack of efficacy of the agent on clinical stability or delay of cognitive or functional decline of participants with mild and moderate AD. 74 Another strategy directed at diminishing the accumulation of Aβ in the brain is based in altering the transportation of Aβ through the BBB.…”
Section: Reduction Of Aβ-plaque Burden Via Drugs Interfering With Metmentioning
confidence: 99%
See 3 more Smart Citations
“…Intravenous immunoglobulin is obtained from plasma of healthy donors and is made up of human Abs mainly of the IgG-type. 5,74 Nevertheless, the first completed phase 3 trial of IVIg as a treatment for AD demonstrated good tolerability but lack of efficacy of the agent on clinical stability or delay of cognitive or functional decline of participants with mild and moderate AD. 74 Another strategy directed at diminishing the accumulation of Aβ in the brain is based in altering the transportation of Aβ through the BBB.…”
Section: Reduction Of Aβ-plaque Burden Via Drugs Interfering With Metmentioning
confidence: 99%
“…5,74 Nevertheless, the first completed phase 3 trial of IVIg as a treatment for AD demonstrated good tolerability but lack of efficacy of the agent on clinical stability or delay of cognitive or functional decline of participants with mild and moderate AD. 74 Another strategy directed at diminishing the accumulation of Aβ in the brain is based in altering the transportation of Aβ through the BBB. A recent therapeutic method performs plasma exchange (PE) with albumin replacement, inducing the shifting of the existing dynamic equilibrium between plasma and brain Aβ.…”
Section: Reduction Of Aβ-plaque Burden Via Drugs Interfering With Metmentioning
confidence: 99%
See 2 more Smart Citations
“…Strict inclusion criteria were applied, such as biomarker evidence of AD pathology, specifically "amyloid positivity," and enrollment of individuals with preclinical stages of the disease. Furthermore, the studies' design became more specific and targeted: the characteristics of amyloid related imaging abnormalities (ARIA) were associated with antibody dose and APOε4 genotype, necessity for higher dosing and evidence for target engagement (e.g., reduction of plaque burden on amyloid PET) was required [5,21].…”
Section: Inadequate Understanding Of the Complex Pathophysiology Of Amentioning
confidence: 99%